Waste Disposal Rate of Small Fishing Vessel ( < 5GT) in PPN Karangantu - Ani Rahmawati; Hery S Nurdin (Jurnal Perikanan dan Kelautan, 2018)
The research was conducted to know waste disposal for small fishing vessel (< 5GT) in PPN Karangantu. Research is done in August until November at PPN Karangantu. The aim for the research is analizing waste disposal rate of small fishing vessel (<5GT) at PPN Karangantu. Methods used in research is the survey method and laboratory analysis. Waste disposal a ship were analysed in the water out of a ship and waters in the area of a ship are docked. The parameter that is a ammonia, magnesium, copper , zinc , phenol , oils and fats. The ammonia in waters higher than the ammonia on a ship waste water. Magnesium, copper, zinc, fatty oil and phenol inversely proportional to the waste water ammonia of value in a ship is higher than in waters